Pengaruh Kegiatan Kokurikuler dalam Mendukung Kegiatan Intrakurikuler di SMAN 1 Seputih Mataram - Reni Anggraini; Berchah Pitoewas; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2018)
The purpose of this research in order to understand the influence of the provision of activities are to be implemented kokurikuler in support the activities of intrakurikuler at the senior high school the land of 1 seputih mataran the new school term of  2017 / 2018.Research methods that were used method of descriptive of quantitative a subject of study student of class x and xi for the mortgage bankers association 45 of the coders .The technique of the collection of data using other of any economic indicators and techniques of such high associated is the objective of the interview .Based on the research done it can be seen that , the imposition of duties kokurikuler can help students coming from poor a better understanding of the the material that was delivered the teacher who was responsible.Tujuan penelitian ini untuk mengetahui pengaruh pemberian kegiatan kokurikuler dalam mendukung kegiatan intrakurikuler di SMA Negeri 1 Seputih Mataran tahun pelajaran 2017/2018. Metode penelitian yang digunakan metode deskriptif kuantitatif dengan subjek penelitian siswa kelas X dan XI yang berjumlah 45 orang responden. Teknik pengumpulan data menggunakan angket dan teknik penunjang adalah wawancara. Berdasarkan hasil penelitian dapat diketahui bahwa, pemberian tugas kokurikuler dapat membantu siswa  lebih memahami materi yang disampaikan oleh guru.Kata kunci: Kegiatan, Kokurikuler, Intrakurikuler.